Larsen Syndrome: A Rare Case Report - Poudel, Bishnu; Sundas, Sunanda; Rai, Amita; Lath, Tripti; Shah Kalwar, Mahalaxmi (Journal of BP Koirala Institute of Health Sciences, 2024)
Larsen syndrome is a rare form of osteochondrodysplasia presenting with features like frequent joint dislocation and craniofacial anomalies. Here, we report a case of five-year-old female diagnosed previously as Larsen syndrome by genetic analysis, who presented with multiple missing and malformed teeth and flexible large joints.